The case for harmonizing the international regulation of mining - Robert Milbourne (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2015)
There is a clear need for international coordination of standards and policies in the mining sector. This Perspective addresses how harmonization may help to reduce arbitrage and promote natural resource investment in a way that minimizes negative impacts on communities and maximizes development gains.
Keywords: 330